Lessons learned from implementing service-oriented clinical decision support at four sites: A qualitative study. Issue 11 (November 2015) - Wright, Adam; Sittig, Dean F.; Ash, Joan S.; Erickson, Jessica L.; Hickman, Trang T.; Paterno, Marilyn; Gebhardt, Eric; McMullen, Carmit; Tsurikova, Ruslana; Dixon, Brian E.; Fraser, Greg; Simonaitis, Linas; et al.
Highlights We used qualitative methods to study the implementation of a service-oriented clinical decision support system. A service-oriented approach to sharing clinical decision support proved feasible in a real-world trial at four different sites. Eight best practices for developers and implementers of service-oriented clinical decision support were identified: (1) optimize performance, or make asynchronous calls, (2) be liberal in what you accept (particularly for terminology), (3) foster clinical transparency, (4) develop a legal framework, (5) support a flexible front-end, (6) dedicate human resources, (7) support peer-to-peer communication, (8) improve standards.